The effectiveness of schema-based counseling model on marriage doubts and attitudes - Paknejad, Samin; Mirzahoseini, Hassan; Monirpour, Nader (Journal of Assessment and Research in Applied Counseling (JARAC), 2020)
Aim: This study aimed to determine the effectiveness of the schema-based counseling model on marriage doubts and attitudes. Method: The design of this quasi-experimental study was with the experimental and control groups and the statistical population of the study included 30 experts and engineers of member companies of the Iranian Society of Consulting Engineers who were hesitant in choosing a spouse, which was selected by purposive sampling method and used in two experimental and control groups (15 people in each group). The data collection tool was Park and Rosen’s (2012) Marriage Attitude Questionnaire and data analysis was performed using a multivariate covariance test. Results: The results showed that there is a significant difference after the test (P <0.001) between the two groups of experts and engineers in the component of positive attitudes, the component of negative attitudes, the component of fears and doubts, the component of love story, the component of respect, the component of trust, the component of finance, the component of purpose and the component of physical intimacy. Conclusion: Conflicts and rumination regarding the choice of spouse and marriage can cause job performance, low efficiency, frustration, fatigue, burnout and, dissatisfaction among experts and engineers due to the volume of professional responsibilities.